Hereditary angioedema in Austria: prevalence and regional peculiarities. (18th March 2019) - Schöffl, Clemens; Wiednig, Michaela; Koch, Lukas; Blagojevic, Daniel; Duschet, Peter; Hawranek, Thomas; Kinaciyan, Tamar; Öllinger, Angela; Aberer, Werner
Summary: Background: Data on the prevalence and clinical features of Austrian patients with hereditary angioedema (HAE) with C1‐inhibitor (C1‐INH) deficiency (HAE‐1) or dysfunction (HAE‐2) are lacking. Methods: Current baseline data were collected in a national survey. The records of HAE patients at the Medical University of Graz were analyzed with regard to clinical characteristics. Results: A total of 137 patients were identified, yielding a prevalence of 1 : 64, 396. The median age at the onset of symptoms was 6.5 years, and the median age at the time of correct diagnosis 21.0 years. The median delay in diagnosis was 15.0 years for newly diagnosed patients without a family history of HAE. Patients with a family history of HAE received an immediate diagnosis. HAE patients without a family history of HAE and born before 1960 had to wait a median of 16.0 years until they were diagnosed correctly. Patients born after 1980 still experienced a median diagnostic delay of 6.5 years. Conclusion: Patients with this condition still face an excessive diagnostic delay in some parts of Austria, or their disorder may even remain unrecognized by specialists. This underlines the need for better awareness of the disease.